Developing and Strengthening Networks to Promote Resilience After Disasters - Angela B. Lindsey; Samantha Goldenberg; Cassie Wandersee (EDIS)
The HGHC series includes thirteen publications that focus on the work of the community outreach and dissemination team, including community engagement, outreach, and research result dissemination. This 3-page document focuses on developing and strengthening networks before they are challenged to promote resilience in and after a disaster. Written by Angela B. Lindsey, Samantha Goldenberg, and Cassie Wandersee, and published by the UF/IFAS Department of Family, Youth and Community Sciences, April 2018. http://edis.ifas.ufl.edu/fy1477